Analysis of the Impact of Fintech Innovation, Digital Trust, and Consumer Education on the Financial Performance of MSMEs in Tangerang City - Saleha, Dwi; Ahmad, Ahmad; Solihin, Solihin; Marsiwi, Dwiati; Sudarmanto, Eko; Noor, Surya Ramadhan (West Science Interdisciplinary Studies, 2026)
The rapid development of financial technology (fintech) has transformed the way Micro, Small, and Medium Enterprises (MSMEs) manage their financial activities, particularly in urban areas such as Tangerang City. This study aims to examine the impact of fintech innovation, digital trust, and consumer education on the financial performance of MSMEs. A quantitative research approach was employed using primary data collected from 150 MSME owners and managers in Tangerang City through a structured questionnaire measured on a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results reveal that fintech innovation has a positive and significant effect on MSME financial performance. Digital trust also shows a significant and positive influence and emerges as the strongest determinant of financial performance. In addition, consumer education significantly contributes to improved financial performance by enhancing financial literacy and the effective use of digital financial services. Collectively, these findings indicate that MSME financial performance in the digital era is driven by an integrated framework combining technological innovation, trust in digital systems, and human capital development. The study provides practical insights for policymakers, fintech providers, and MSME stakeholders in developing inclusive and sustainable digital financial ecosystems.